2007
DOI: 10.1016/j.molimm.2006.04.025
|View full text |Cite
|
Sign up to set email alerts
|

Cardamonin inhibits COX and iNOS expression via inhibition of p65NF-κB nuclear translocation and Iκ-B phosphorylation in RAW 264.7 macrophage cells

Abstract: Cardamonin, a chalcone isolated from the fruits of a local plant Alpinia rafflesiana, has demonstrated anti-inflammatory activity in cellular models of inflammation. In this report, we evaluated the ability of cardamonin to suppress both NO and PGE2 synthesis, iNOS and COX-2 expression and enzymatic activity, and key molecules in the NF-kappaB pathway in order to determine its molecular target. Cardamonin suppressed the production of NO and PGE2 in interferon-gamma (IFN-gamma)- and lipopolysaccharide (LPS)-ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 175 publications
(113 citation statements)
references
References 27 publications
5
101
0
2
Order By: Relevance
“…NF-κB is present as a complex with IκB located in the cytoplasm in unstimulated cells. When stimulated, IκB is phosphorylated, ubiquitinated and rapidly degraded, which releases the p65 subunit of NF-κB from IκB, resulting in p65 translocation into the nucleus where it regulates gene transcription (26,27). To explore the mechanism of NF-κB inactivation by TFHDW, the effects of the extract on the LPS-induced phosphorylation of p65 and IκB were examined by western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is present as a complex with IκB located in the cytoplasm in unstimulated cells. When stimulated, IκB is phosphorylated, ubiquitinated and rapidly degraded, which releases the p65 subunit of NF-κB from IκB, resulting in p65 translocation into the nucleus where it regulates gene transcription (26,27). To explore the mechanism of NF-κB inactivation by TFHDW, the effects of the extract on the LPS-induced phosphorylation of p65 and IκB were examined by western blotting.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal physiological conditions, NF-kB forms a cytoplasmic complex with its inhibitors, the IkBs. Once the IkBs become phosphorylated, NF-kB is released and translocates to the nucleus where its target genes are then activated (Israf et al, 2007). Our study results indicated that sophocarpine not only decreased MMP-2 and MMP-9 levels but also inhibited p-IKBa expression in AC rats.…”
Section: Discussionmentioning
confidence: 50%
“…3 Cardamonin's name comes from the fact that it can be found in cardamom spice (Fig. 4), but since the first article where it was described, 22 it has been found in many other (some of them edible) plant species, such as Alpinia blepharocalyx, 23,24 Alpinia gagnepainii, 25 Alpinia conchigera, 26,27 Alpinia hainanensis, [28][29][30][31][32][33][34][35][36][37][38][39][40] Alpinia malaccensis, 41 Alpinia mutica, 42,43 Alpinia pricei, 44 Alpinia rafflesiana, [45][46][47][48] Alpinia speciosa, 22,49,50 Amomum subulatum, 51 Artemisia absinthium, 52 Boesenbergia pandurata, [53][54][55][56][57][58][59][60] Boesenbergia rotunda, 61,62 Carya cathayensis, 63 Cedrelopsis grevei, 64 Combretum apiculatum, 65 Comptonia pere...…”
Section: Sources Of Cardamoninmentioning
confidence: 99%
“…83 Its interference over the NF-jB pathway and subsequently, the p65NF-jB protein cellular distribution inhibits cyclooxygenase-2 and inducible nitric oxide synthase. 47 It also appears to end up inhibiting prostaglandin E2, tumor necrosis factor a (TNF-a) release, thromboxane B2 production, and intracellular reactive oxygen species generation, all in a dose-dependent manner. 48,54 In most of these studies, RAW264.7 cells were used and analyzed by enzyme-linked immunosorbent assays, western blotting, and interestingly, luciferase gene reporter assays.…”
Section: Health Applicationsmentioning
confidence: 99%